2007
DOI: 10.1007/s12019-007-8008-5
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Acute Retinopathy of Prematurity

Abstract: We prospectively studied the risk factors and the incidence of retinopathy of prematurity (ROP) in 195 consecutive preterm infants. Birth weight and duration of mechanical ventilation were the only factors that were significantly associated with the incidence of ROP. While indomethacin increases the risk of developing ROP, maternal antenatal steroids have a protective effect against the development of severe stages of ROP. The presence of intraventricular hemorrhage increases the risk of severe ROP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 32 publications
2
11
1
Order By: Relevance
“…Most studies have demonstrated that prematurity and low BW are the strongest predictive factors of ROP ( 19 21 ). Other factors associated with ROP include prolonged mechanical ventilation ( 22 24 ), the need for nasal CPAP ( 25 , 26 ), development of BPD ( 27 , 28 ), sepsis ( 29 ), hyperoxia ( 30 ), hypoxia ( 31 ), hypercapnia, and acidosis. Higher rates of ROP were found in infants with longer length of initial hospital stay ( 32 , 33 ), and prolonged parenteral nutrition, which are a proxy for cumulative illness burden.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies have demonstrated that prematurity and low BW are the strongest predictive factors of ROP ( 19 21 ). Other factors associated with ROP include prolonged mechanical ventilation ( 22 24 ), the need for nasal CPAP ( 25 , 26 ), development of BPD ( 27 , 28 ), sepsis ( 29 ), hyperoxia ( 30 ), hypoxia ( 31 ), hypercapnia, and acidosis. Higher rates of ROP were found in infants with longer length of initial hospital stay ( 32 , 33 ), and prolonged parenteral nutrition, which are a proxy for cumulative illness burden.…”
Section: Discussionmentioning
confidence: 99%
“…10,13,39,57,71,74,109,114,131,149,152,167,231,236,257,264,276,283,312,313,315,364,401,412,428 Similarly, many studies identified prolonged mechanical ventilation as a risk factor for any or severe ROP. 11,12,36,39,53,57,106,120,157,167,187,211,232,263,266,274,275,286,335,337,345,348,368,370,405,406,412,417…”
Section: Major Risk Factorsmentioning
confidence: 99%
“…Prolonged mechanical ventilation (PMA), often defined as >7 days of ventilator dependence, is among the most frequently identified risk factors for ROP. 12,24,26,35,54,106,117,120,137,148,157,174,184,187,211,220,233,254,257,263,266,286,345,348,370,397,405,412,413,417 A recent cohort study including 979 infants revealed that the need for respiratory support including mechanical ventilation and high-frequency oscillatory ventilation at time of first study-related examination (median 33 weeks PMA) was an independent risk factor for referral-warranted ROP. 417 Several studies have found that, like traditional mechanical ventilation, the need for nasal CPAP also increases the risk of ROP, 150,174,220,233,275,337,363 and delays involution of ROP.…”
Section: Alternative Risk Factorsmentioning
confidence: 99%
See 2 more Smart Citations